Vitamins C and E Associated With Cryotherapy in the Recovery of the Inflammatory Response After Resistance Exercise: A Randomized Clinical Trial. Issue 1 (5th January 2022) - de Brito, Edineia; Teixeira, André de Oliveira; Righi, Natiele Camponogara; Paulitcth, Felipe da Silva; da Silva, Antonio Marcos Vargas; Signori, Luis Ulisses
Abstract: de Brito, E, Teixeira, AdO, Righi, NC, Paulitcth, FdS, da Silva, AMV, and Signori, LU. Vitamins C and E associated with cryotherapy in the recovery of the inflammatory response after resistance exercise: A randomized clinical trial. J Strength Cond Res 36(1): 135–141, 2022—The objective of this research was to compare the effects of cryotherapy associated with vitamins (C and E) on the recovery of the inflammatory response from the resistance exercise (RE) session of untrained volunteers. Fourteen subjects (26.2 ± 5 years old, 25.8 ± 3 kg·m −2 ) underwent 4 sessions of RE with different forms of recovery. The RE consisted of 4 sets of 10 maximal repetitions for each exercise (extensor bench, squat, and leg press). The recoveries were randomized and comprised the passive (control), with vitamins C (1 g) and E (800 UI) supplementation 40 minutes before exercise, with cryotherapy (immersion in water 15° C for 10 minutes), and the association (vitamins and cryotherapy). Hemogram, inflammatory markers (C-reactive protein and creatine kinase [CK]), and parameters of oxidative stress (lipid peroxidation [LPO] and antioxidant capacity against radical peroxyl) were evaluated before (baseline) and after (0, 30, and 120 minutes) the RE sessions. Muscle pain (primary outcome) was evaluated 24 hours after exercise. C-reactive protein ( p = 0.010) and LPO ( p < 0.001) increased (120 minutes) only in passive recovery. Recovery with cryotherapy (30 minutes), with vitamins and the association (0 and 30 minutes) delayed increases in CK ( p < 0.001). Antioxidant capacity against radical peroxyl increased (30 minutes) only in recovery with the association ( p < 0.011). The pain decreased in the recoveries with cryotherapy and association ( p < 0.001). The association of vitamins (C and E) with cryotherapy attenuated the inflammatory response and pain, favoring recovery after an acute RE session.